Causative Agents of Onychomycosis: A 7‐Year Study. Issue 6 (13th April 2016) - Chadeganipour, Mostafa; Mohammadi, Rasoul
Abstract : Background: Onychomycosis is principally caused by dermatophyte species, but nondermatophyte molds and yeasts have also been involved, causing different clinical manifestations. The aim of this investigation is to determine the clinicomycological and epidemiological profile of the etiologic agents of onychomycosis. Methods: The study population included 9, 785 suspected cases of onychomycosis referred to the Medical Mycology Reference Laboratory in Isfahan, Iran, during 2007–2014. Nail clipping was collected in sterile Petri dishes for direct microscopic examination and culture. Clinical isolates were identified by using phenotypic tests and molecular techniques. Results: Of total 9, 785 cases with clinical suspicion of onychomycosis comprised in the present study, 1, 284 patients (13.1%) were positive by direct microscopy. Age range of patients was between 1 and 82 years. Housewives were the commonest infected population. Candida albicans was the most prevalent species isolated from patients in this study (34.9%) followed by Trichophyton interdigitale (11.7%) and Aspergillus flavus (9.1%). Conclusion: The pattern of causative agents and clinical signs of onychomycosis is altering region to region, so repeated epidemiological surveys of onychomycosis seems to be fundamental. The present study provides novel and appropriate epidemiologic data of onychomycosis for the better prevention and treatment of this fungal infection.